Symbiosis Between Nature and Humanity in the Socio-Ecocritical Reading of Three Songs by Víctor Jara - Allende Pino, Cristóbal; Rodríguez Droguett, Elvira (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The present article proposes a socio-ecocritical approach to the lyrics of three songs by the Chilean singer-songwriter Víctor Jara: “El arado”, “El pimiento” and “Angelita Huenumán”. The analysis of the representations and the literary figures arranged in the letters allows us to determine a symbiosis between nature and humanity, a relationship also mediated in many cases by the act of working. The poetic proposal of Víctor Jara is revolutionary against the traditionalist and nostalgic conceptions of nature held by other musical currents, such as “popular music”. At the same time, the context of production of the songs, marked by the processes of the Chilean land reform, allows stressing the notions about land ownership, and the relationship that society establishes with nature. These questions remain present in the current context of environmental crisis; moreover, revisiting the Víctor Jara’s songs enables us to imagine new possible worlds.